Controllable synthesis of Ag/AgCl@MIL-88A via in situ growth method for morphology-dependent photocatalytic performance. Issue 18 (16th April 2019) - Wu, Wubin; Wang, Jingchao; Zhang, Tianyong; Jiang, Shuang; Ma, Xiaoyuan; Zhang, Guanghui; Zhang, Xia; Chen, Xingwei; Li, Bin
Abstract : Several different fusiform-shaped Ag/AgCl@MIL-88A (ACML) materials with good photocatalytic activity were prepared successfully by using the in situ growth method. Abstract : Different fusiform-shaped MIL-88A materials were successfully prepared by adjusting the mole ratio of the central metal ion and the organic ligand and using different polar solvents. With differently shaped MIL-88A supports, several Ag/AgCl@MIL-88A (ACML) were prepared successfully using the in situ growth method. These ACML composites showed a good photocatalytic activity under the simulated sunlight and visible light. The employment of Cl − ions, anchored on the surface of MIL-88A, could improve the dispersion and stability of the loaded Ag/AgCl nanoparticles. The s-ACML composite showed excellent photocatalytic stability during the cycle tests. The in situ growth strategy provided a facile method to design and synthesize MOF composite photocatalysts for wastewater treatment. In addition, based on the related optical and electrical characterization analysis, a possible mechanism of the ACML composite photocatalytic activity was proposed.